Cutaneous manifestations of phosphate solution extravasation. (1st January 2018) - Verykiou, S.; Aljefri, K.; Gopee, H.; Taheri, L.; Charlton, F.; Langtry, J. A.; Blasdale, C.
Summary: Extravasation injuries are common in patients receiving multiple intravenous infusions. Although such injuries are closely associated with the infusion of cytotoxic chemotherapy, they have also been been associated with extravasation of noncytotoxic drugs. Extravasation injuries can lead to skin ulceration and nerve and tendon damage, and therefore to permanent disability. We report three cases of phosphate solution extravasation leading to unusual cutaneous manifestations.